Comparing reactogenicity of COVID-19 vaccines: a systematic review and meta-analysis. (2nd September 2022) - Sutton, Natalina; San Francisco Ramos, Alberto; Beales, Emily; Smith, David; Ikram, Sabina; Galiza, Eva; Hsia, Yingfen; Heath, Paul T.
ABSTRACT: Objectives: A number of vaccines have now been developed against COVID-19. Differences in reactogenicity and safety profiles according to the vaccine technologies employed are becoming apparent from clinical trials. Methods: Five databases (Medline, EMBASE, Science Citation Index, Cochrane Central Register of Controlled Trials, London School of Hygiene and Tropical Medicine COVID-19 vaccine tracker) were searched for relevant randomized controlled trials between 1 January 2020 and 12 January 2022 according to predetermined criteria with no language limitations. Results: Forty-two datasets were identified, with 20 vaccines using four different technologies (viral vector, inactivated, mRNA and protein sub-unit). Adults and adolescents over 12 years were included. Control groups used saline placebos, adjuvants, and comparator vaccines. The most consistently reported solicited adverse events were fever, fatigue, headache, pain at injection site, redness, and swelling. Both doses of mRNA vaccines, the second dose of protein subunit and the first dose of adenovirus vectored vaccines were the most reactogenic, while the inactivated vaccines were the least reactogenic. Conclusions: The different COVID-19 vaccines currently available appear to have distinct reactogenicity profiles, dependent on the vaccine technology employed. Awareness of these differences may allow targeted recommendations for specific populations. Greater standardization of methods for adverse event reporting will aid future research in this field.